2014
DOI: 10.1136/tobaccocontrol-2014-051675
|View full text |Cite
|
Sign up to set email alerts
|

How popular is waterpipe tobacco smoking? Findings from internet search queries

Abstract: Objectives Waterpipe tobacco smoking (WTS), a traditional tobacco consumption practice in the Middle East, is gaining popularity worldwide. Estimates of population-level interest in WTS over time are not documented. We assessed the popularity of WTS using World Wide Web search query results across four English-speaking countries. Methods We analysed trends in Google search queries related to WTS, comparing these trends with those for electronic cigarettes between 2004 and 2013 in Australia, Canada, the UK an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 31 publications
0
42
0
2
Order By: Relevance
“…In the past decade, waterpipe smoking has become a global phenomenon among youth, many of whom are unaware of the health risks associated with this form of tobacco consumption (Maziak et al 2015; Salloum et al 2014; Salloum et al 2015b). There are currently no evidence based warning label requirements for waterpipe products, whereas warnings on cigarette packaging is a major form of communicating tobacco-related health risks to users and others exposed to their smoke (Hammond et al 2006; O’Hegarty et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, waterpipe smoking has become a global phenomenon among youth, many of whom are unaware of the health risks associated with this form of tobacco consumption (Maziak et al 2015; Salloum et al 2014; Salloum et al 2015b). There are currently no evidence based warning label requirements for waterpipe products, whereas warnings on cigarette packaging is a major form of communicating tobacco-related health risks to users and others exposed to their smoke (Hammond et al 2006; O’Hegarty et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Waterpipe smoking (also known as hookah, shisha, and narghileh) is increasing in popularity in the United States, with the highest prevalence rates reported among college students (Maziak et al, 2015; Salloum et al, 2014). Waterpipe smoke contains many of the same toxicants as cigarette smoke (Shihadeh et al, 2015), and waterpipe smoking has been associated with respiratory and cardiovascular illnesses, periodontal disease, and obstetric and perinatal complications (Akl et al, 2010; El-Zaatari et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Krauss et al, analysed chatter content about shisha on twitter. Analysis showed that 19% were advertisements/ promotions for shisha venues/ products 13 . Shisha venues providing catering services to birthday parties and wedding functions should be considered as worrying trend.…”
Section: Resultsmentioning
confidence: 99%
“…Independent sample t test assuming equal variances was used on the data collected with a p value set at 0.05. Simple descriptive statistics of the observed findings were analysed using MedCalc 13 .…”
Section: Methodsmentioning
confidence: 99%